The Forms of Gender Injustice in Family Relations - Irfan Firdaus, Muhammad; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The family is the smallest social unit and serves as the primary foundation for shaping character and values within society. Ideally, family relationships are built on balanced and just interactions among members. However, in practice, gender inequality remains prevalent in various aspects of family life. This includes unequal division of roles, exclusion of women from decision-making processes, disproportionate domestic workloads, and experiences of violence against women. This study aims to identify and analyze the forms of gender injustice within family relations and to explore strategic efforts to achieve gender equality. Utilizing a descriptive qualitative approach and library research methods, this study examines literature, legal documents, and previous research through the lens of gender theory and family sociology. The findings reveal five major forms of gender injustice: marginalization, subordination, stereotypes, violence, and excessive workloads. These issues have a systemic impact on the well-being of family members, particularly women and children. Addressing these challenges requires a proper understanding of gender concepts, equitable distribution of domestic responsibilities, shared decision-making, and transparent financial management. Promoting equality within the family not only fosters emotionally and socially healthy individuals but also contributes to the development of an inclusive, harmonious, and gender-just society.